The Climate-Smart Village approach nominates to the GCIAR's 50 greatest innovations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Integrated into CCAFS programmatic ToC and Regional Impact pathways since 2015 as a mechanism to roll out CSA and translate reserach into development outcomes, this innovation has been promoted by a large number of public and private sector organizations potentially benefiting millions of farmers in thousands of locations worldwide.